Comparative analysis of antioxidant properties, quality attributes and yield of organically and conventionally grown melons (Cucumis melo L.) and tomatoes (Solanum lycopersicum L.) - Salandanan, Karen A., author; Stushnoff, Cecil, advisor; Bunning, Marisa, committee member; Wallner, Stephen J., committee member (Colorado State University. Libraries, 2008)
Fresh fruits and vegetables including melons and tomatoes have gained considerable prominence in the American diet due to increasing awareness of their potential health and nutrition benefits. Consumers are starting to take a closer look not only at organoleptic qualities but also at nutritional value of the produce. This new trend of consumer preference for healthier food choices is one of the driving forces of the organic industry. Organically grown fruits and vegetables are perceived to be more nutritious than those that are produced under conventional production system. Comparison studies on selected fruit and vegetable crops have been carried out to examine this claim. However, verifiable results from well-designed experiments were very limited in many crops, including tomatoes and melons. This research assessed the difference in the antioxidant properties, quality attributes, and yield of organically and conventionally grown tomatoes and melons. Nutritionally superior cultivars were also identified which could be beneficial for small and medium sized farmers. Ten commercial cultivars of tomatoes were grown in 2005 and 2006, under certified organic and conventional production systems at the Horticulture Field Research Center, Colorado State University, Colorado USA. Melon and tomato cultivars were analyzed for their ascorbic acid, total phenolic content, Trolox equivalent antioxidant capacity (TEAC), percent dry matter, soluble solids content, and yield. A 3 to 6 fold difference in ascorbic acid, total phenolic content, and antioxidant activity was observed both in melon and tomato cultivars. Melons grown organically had significantly higher ascorbic acid when both years were combined while total phenolic content was significant only in the first year. In tomatoes, higher antioxidant activity was observed in organically grown tomatoes while yield and soluble solids concentration was higher under the conventional production system. Lower yield was observed in melon and tomato cultivars with higher antioxidant content and activity suggesting a possible trade- off between yield and nutrients. Compared to genotype, production system had less influence on antioxidant properties and fruit quality attributes. A significant interaction between cultivar and production system would likewise imply that some cultivars when grown organically or conventionally could have higher antioxidant content and activity. Thus, choice of cultivar was the most important contributor to high antioxidant properties. Based on the antioxidant index that we have developed as a tool to rank the cultivars in terms of antioxidant content and activity, the top melon cultivars, regard less of year or production system, are the following: 'Savor', 'Sweetie#6', 'Early Queen', 'Edonis' and 'Rayan'; while ' Jet Star', 'New Girl', 'Fanstastic', 'First Lady', and 'Celebrity' were determined to be nutritionally superior tomatoes. These nutritionally superior cultivars with high antioxidant levels may provide a competitive marketing and supply niche for small fam1 producers. Future initiatives could involve screening of tomato and melon cultivars for higher antioxidant content that could be utilized in breeding programs.
Covers not scanned.
Keywords: Organic farming; Antioxidants; Muskmelon; Tomatoes